Pemetaan Konsumen Berdasarkan Perilaku Transaksi Produk Ritel Pada Distributor XYZ Semarang - Yanuangga Galahartlambang; Titik Khotiah; Jumain Jumain (Jurnal JEETech, 2022)
Customer segmentation is essential for any business to better understand their customers, to maintain customer satisfaction, and to develop product and service needs. The purpose of customer segmentation is to determine how to handle customers in each category to increase each customer's profit for the business. Distributor XYZ Semarang is a multi-branched company engaged in the sale of consumer retail products to serve customers from small (retail) to large (wholesale) businesses. The database used in this study was taken from one branch with a transaction period of 2 years. The purpose of this research is to build a customer segmentation model based on customer demographics and transaction behavior and to help businesses better understand their customers to support marketing strategies. The proposed segmentation model is regarding customer demographic data regarding Recency, Frequency, and Monetary (RFM) resulting from purchasing behavior, customers have been segmented using the K-means grouping technique into various groups based on their similarities, and profiles for each group are identified based on their characteristics. . Thus, companies can find out the behavior of customers from the results of grouping based on how much value they spend, how often they make purchases and what products are their shopping concerns where this can be used as an evaluation basis for marketing strategies and further analysis..